PENATAAN DAN PEMBINAAN MINIMARKET DI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI TAHUN 2016 - Pranata, Iwi; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Indonesia as one of developing countries, did not spared the target of the modern market. The development of modern market in Indonesia the last few years it can be said to grow very rapidly. Almost all over the city of Indonesia is flooded by modern markets with various type and models. The development of modern store does have real advantages and disadvantages. The favorable side of increasing local revenue, expanding new jobs. But, on the other hand it is existence can harm the small traders. If it is left alone, then existence of a modern market will evict of small traders.In Kuantan Singingi Regency, the local government is the most competent in the implementation of Presidential Regulation No. 112 of 2007 on the arrangement and fosreing of traditional markets, shopping centers and modern stores. As well as the regulation of the Minister of Trade No. 70 of 2013 on arrangement and fosreing of traditional markets, shopping centers and modern stores.The purpose in this research is to describe (1) Structuring and Development of minimarket in Kuantan Tengah of Kuantan Singingi in 2016. (2) Constraints in structuring and development of minimarket in Kuantan Tengah of Kuantan Singingi in 2016.The research is qualitative research method. The research was conducted in Taluk Kuantan area, Kuantan Tengah of Kuantan Singingi Regency. The techniques used to collect the data in this study are (1) Interview, (2) Library Studies, and (3) Documentation.Based on the result, the researcher found that the study indicate that in minimarket facilities and development there are still many violations. There are (1) 6 minimarket that do not yet have a modern store business license (IUTM) but still operate. (2) 3 minimarket that already have a modern store business license (IUTM) and there is 1 minimarket in the process of IUTM. (3) Kuantan Singingi does not have Spatial Plan (RTRW).Keywords : Policy, Stucturing and Development of Minimarket.